Determination of Consumer Switching Barriers to Use Prepaid Electricity Systems in the Household Sector in Makassar, Indonesia - Karim, Kasnaeny; Tajibu, Muhammad Jibril; Akhmad, Akhmad (International Journal of Energy Economics and Policy, 2020)
A new alternative of electricity bill payment exists in Indonesia at present, namely prepaid systems. The system is intended to facilitate customers in electricity saving where the electricity utilization could be adjusted. In reality, however, post-paid electricity system utilization still receives great demand. As a consequence, it could not suppress electricity consumption. This research aims to learn factors inhibiting consumers to switch to prepaid electricity systems for their electricity consumption. A descriptive research carries out to answer the research problems. Sample consists of 100 people determined via a snowball sampling technique. Data collection is conducted using questionnaires and measured using Likert Scale of 1-5. Factory analysis is used as an analysis tool. The research results indicate that the main factor that becomes a barrier for electricity customers to switch to prepaid systems is habitual using factor. Switching cost factor, lack of prepaid system information, and relationship and reputation of post-paid products are the second, third, and fourth factors, respectively. Keywords: Switching barrier, electricity, prepaid, and household sector JEL Classifications: C42, D10, M00, O30 DOI: https://doi.org/10.32479/ijeep.10237